[PP.36.13] NONINVASIVE METHODS FOR ENDOTHELIAL FUNCTION ASSESSMENT IN PATIENTS WITH RISK FACTORS FOR ATHEROSCLEROSIS. (September 2016) - Wilk, G.; Osmenda, G.; Nowak, M.; Rajch, D.; Sliwa, T.; Mikolajczyk, T.; Czesnikiewicz-Guzik, M.; Guzik, T.
Abstract : Objective: While various methods are available for assessment of endothelial function in patients with atherosclerosis, some studies suggested that various techniques differ in their ability to detect effects of various risk factors. We aimed to investigate which risk factors for atherosclerosis have greatest effects on measures of individual risk factors (hypertension, diabetes, obesity, smoking and male sex). Design and method: The group of 170 subjects, with a negative history of cardiovascular disease were examined. The mean age was 57.3 ± 6.9; 84 (49.4%) were men. Risk factors were determined from patient history and conformed by biochemical/clinical measurements. Endothelial function was assessed by: Flow Mediated Dilation (FMD) and Nitroglycerin-Mediated Dilatation (bNMD) of the brachial artery; measurement of reactive hyperaemia using Peripheral Arterial Tonometry (LnRHI) with Endo-PAT 2000 and by assessment of Pulse Wave Velocity (PWV) using SphygmoCor EM3. Carotid artery Intima Media Thickness (IMTmean) was measured as a measure of sub-clinical atherosclerosis. Results: There was a significant correlation between the number of risk factors and the bFMD value (r = -0.450; p = 0.001), IMT mean (r = 0.305; p = 0.001) and LnRHI (r = -0.219; p = 0.004) and PWV (r = 0.165; p = 0.031). Statistically significant differences between the average values of the tests performed and atherosclerosis risk factors presented in the table below. There was no statistical differences in testing for dyslipidemia. All measures apart from LnRHI correlated to IMTmean. Figure. No caption available. Conclusions: The study established that bFMD is most strongly affected by classical risk factors for atherosclerosis, while relative hyperaemia index (LnRHI) was different only in relation to obesity and diabetes.